The Qur’an in the Modern Era: A Critical Analysis of Contemporary Interpretations - Bamba, Abdoulaye (Jurnal Studi Al-Qur’an, 2024)
The Qur’an, the sacred book of Muslims, is considered the primary source of divine knowledge and religion. It has been the subject of extensive study by scholars of various disciplines for decades. To preserve the faithful transmission of his teachings, strict rules have been established to which all scholars must conform. However, in recent decades, some works have emerged which are subject to inconsistency with the carefully established rules. In this article, we will focus on a critical and scientific approach to certain opinions and ideas formulated in the books of NICOLAÏ Sinai, entitled "The Qur’an: A historical-critical Introduction" and Abdullah Saeed, entitled "The Qur’an: An Introduction." This article aims to present an objective and rigorous analysis while highlighting the points of disagreement and the outstanding questions concerning the interpretations presented in these works. From this observation, the article will highlight the discrepancies with some of the concepts advanced in these books using a qualitative research methodology.